Secado de semillas "Citrillus lanatus" (sandía) y su utilización en elaboración de panes fortificados con mix vitaminas/minerales "2019" - Salinas Bardales, Juan Marcos (2021)
he study was carried out in the pilot plant of the FIA-UNAP, using a stationary flow dryer, the raw material being watermelon seeds (Citrillus lanatus) to obtain the data and build the drying curves, using temperatures of drying of 50, 60 and 70oC, after each evaluation the drying curves were put together, being the temperature of 60oC, the one that gave the best results, then that dry flake was ground in a hammer mill, and the pariashysical chemical analysis and finally three baking tests (5, 7.5 and 10%) were carried out, concluding that test 1 is the one that demonstrated the best sensory characteristics , when compared with the other formulations, it was not concluded that there are no differences between each formulation.